Enzymatic testing for mucopolysaccharidosis type I in Kuwaiti newborns: a preliminary study toward newborn screening - Alsharhan, Hind; Haider, Mohammad Z.; Qadoura, Bann; Ayed, Mariam; Dhaunsi, Gursev S.; Alkandari, Hessa (Frontiers in Pediatrics, 2024)
Mucopolysaccharidosis type I (MPS I) is an autosomal recessive lysosomal storage disorder characterized by deficient or absent α-L-iduronidase (IDUA) enzyme activity due to pathogenic variants in the IDUA gene. Early treatment with hematopoietic stem cell transplantation and/or enzyme replacement therapy is associated with improved outcomes in this progressive multisystem disease. The diagnosis is usually delayed due to late presentation and non-specific symptoms, which result in high morbidity and mortality. The incidence of MPS I is unknown in Kuwait. This pilot study was undertaken to screen MPS I in all Kuwaiti neonates born at Farwaniya Hospital (FH), a major center in Kuwait, over 12 months. This study examined the incidence of MPS I for inclusion in the national newborn screening (NBS) to enable its early detection and adequate treatment. All Kuwaiti neonates born at FH between December 2021 and December 2022 were screened for MPS I. The screening consisted of determining IDUA enzyme activity in dried blood spot-derived samples using tandem mass spectrometry. A follow-up genetic analysis of the IDUA gene has been planned to screen the cases with diminished IDUA enzyme activity as second-tier testing. A total of 618 newborns, including 331 (54%) boys and 287 (46%) girls, were screened. Of them, 20 had deficient IDUA enzyme activity but showed negative genetic testing. However, we have diagnosed one additional female infant with MPS I who belonged to FH, but the parents chose to deliver in a private hospital. The molecular genetic study revealed the presence of a previously reported pathogenic nonsense variant in the IDUA c.1882C>T, which is associated with severe phenotype. That being included, MPS I is estimated to be approximately 0.2% of all screened cases in Kuwait. Our study is the first to evaluate the incidence of MPS I in Kuwait. Given the single center, small number of screened infants, and the short study duration thus far, it is premature to calculate the incidence. It is anticipated that as the study continues, we would be able to estimate the incidence in our population correctly. Screening newborns in all maternity hospitals in Kuwait is necessary to calculate the actual incidence of this severe disorder. Still, our preliminary data support the inclusion of MPS I in national NBS program to allow early initiation of treatment and thus improve disease outcome.